Self-referral psychological treatment centre for young adults: a 2-year observational evaluation of routine practice before and after treatment. Issue 8 (17th August 2015) - Halje, Karin; Timpka, Toomas; Tylestedt, Petra; Adler, Anna-Karin; Fröberg, Lena; Schyman, Tommy; Johansson, Kristoffer; Dahl, Katarina
Abstract : Objectives: To examine a self-referral psychological service provided to young adults with regard to effects on anxiety, depression and psychological distress and to explore client factors predicting non-adherence and non-response. Design: Observational study over a 2-year period. Setting: Young Adults Centre providing psychological services by self-referral (preprimary care) to Linköping, Åtvidaberg, and Kinda municipalities (combined population 145 000) in Östergötland county, Sweden. Participants: 607 young adults (16–25 years of age); 71% females (n=429). Intervention: Individually scheduled cognitive behavioural therapy delivered in up to six 45 min sessions structured according to an assessment of the client's mental health problems: anxiety, depression, anxiety and depression combined, or decreased distress without specific anxiety or depression. Primary outcome measures: Pre–post intervention changes in psychological distress (General Health Questionnaire-12, GHQ-12), Hospital Anxiety and Depression Scale Anxiety/Depression (HADS-A/D). Results: 192 clients (32.5%) discontinued the intervention on their own initiative and 39 clients (6.6%) were referred to a psychiatric clinic during the course of the intervention. Intention-to-treat analyses including all clients showed a medium treatment effect size (d=0.64) with regard to psychological distress, and small effect sizes were observed with regard to anxiety (d=0.58) and depression (d=0.57). Restricting the analyses to clients who adhered to the agreed programme, a large effect size (d=1.26) was observed with regard to psychological distress, and medium effect sizes were observed with regard to anxiety (d=1.18) and depression (d=1.19). Lower age and a high initial HADS-A score were the strongest risk factors for non-adherence, and inability to concentrate and thinking of oneself as a worthless person increased the risk for discontinuation. Conclusions: We conclude that provision of psychological services to young people through a self-referral centre has potential to improve long-term mental health in communities, but management of non-adherence remains a central challenge.